2018
DOI: 10.1177/0969733018792739
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating ethical sensitivity in surgical intensive care nurses

Abstract: Background and aim: Surgical intensive care nurses should have ethical sensitivity allowing them to identify ethical issues in order that they can recognize them and make the right decisions. This descriptive study was conducted with the aim of evaluating the ethical sensitivity of surgical intensive care nurses. Materials and methods: The research was carried out with the participation of 160 nurses in six Turkish hospitals, four state, one university, and one private. The data were collected using the “Nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 15 publications
(27 reference statements)
3
31
0
5
Order By: Relevance
“…Moreover, Iranian nurses reported moderate levels of moral sensitivity. In a similar study in Brazil, the moral sensitivity of 100 nurses was examined using a 28-item 2019) also assessed the moral sensitivity of 160 nurses who worked in surgical intensive care units (ICUs) across six Turkish hospitals.They reported moderate levels of moral sensitivity as well as statistical differences for moral sensitivity according to workplace, years of nursing experience, and duration of working in an ICU (Basar and Cilingir, 2019). Morever, in similar studies conducted with paediatric nurses (Arslan and Calpbinici, 2018), clinical nurses (Aksu and Akyol, 2011) and critical care nurses (Borhani et al, 2017) moral sensitivity was found to be moderate.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, Iranian nurses reported moderate levels of moral sensitivity. In a similar study in Brazil, the moral sensitivity of 100 nurses was examined using a 28-item 2019) also assessed the moral sensitivity of 160 nurses who worked in surgical intensive care units (ICUs) across six Turkish hospitals.They reported moderate levels of moral sensitivity as well as statistical differences for moral sensitivity according to workplace, years of nursing experience, and duration of working in an ICU (Basar and Cilingir, 2019). Morever, in similar studies conducted with paediatric nurses (Arslan and Calpbinici, 2018), clinical nurses (Aksu and Akyol, 2011) and critical care nurses (Borhani et al, 2017) moral sensitivity was found to be moderate.…”
Section: Discussionmentioning
confidence: 90%
“…21 Basar and Cilingir also believe that the concept of moral sensitivity consists of commitment to ethical principles, determination in achieving moral outcome, and developing a good understanding of situations. 22 Ineichen believes that sensitivity toward ethics and one’s profession is a significant factor in health systems, and he states that the presence of individuals who are aware of ethical values and are assertive in following them in the system has a critical role in improving the function of healthcare systems. In such systems where being committed to ethical principles is a salient criterion, individuals should be more sensitive toward human values.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Lutzen et al 27 and Buyuk et al 21 reported that people with more experience have higher moral sensitivity in terms of making the right decision in the face of ethical dilemmas. Basar and Cilingir 28 argue that there is a significant difference only in the autonomy sub-dimension of male nurses and that ethical sensitivity is higher in men. They also emphasize that the ethical sensitivity of married nurses is higher than single nurses, that the ethical sensitivity is the highest among nurses working in the surgical intensive care unit for 0-1 year, and that the ethical sensitivity of high school graduate nurses is higher than others.…”
Section: Discussionmentioning
confidence: 99%